G4 اثر الذكاء التنافسي على تحقيق القدرة التنافسية بمؤسسة اتصالات الجزائر بالوادي حول منتوج - بوعسرية احميدة; بلعروسي فراس; هاني اشرف (eloued Of university جامعة الوادي, 2025)
تهدف هذه الدراسة إلى معرفة أثر الذكاء التنافسي على تحقيق القدرة التنافسية في المؤسسات الجزائرية، وقد تم التركيز على الأبعاد الأساسية للذكاء التنافسي والمتمثلة في: ذكاء المنافسين والسوق، الذكاء الاستراتيجي، الذكاء التكنولوجي، بالإضافة إلى أبعاد القدرة التنافسية مثل: الكفاءة المتميزة، الجودة، المرونة، والإبداع والابتكار. تم جمع البيانات الأولية باستخدام استبيان مصمم خصيصًا للدراسة، وُزّع على عينة مكونة من 35 موظفًا في مؤسسة "اتصالات الجزائر"، بالوادي يمثلون مستويات وظيفية مختلفة. وقد تم تحليل البيانات باستخدام برنامج SPSS 28، حيث تم توظيف أساليب الإحصاء الوصفي لقياس واقع الذكاء التنافسي والقدرة التنافسية داخل المؤسسة، كما استُخدمت أساليب الإحصاء الاستدلالي مثل تحليل الانحدار الخطي البسيط لاختبار فرضيات الدراسة. كما اننا استعملنا نموذج IMRAD والمنهج الوصفي التحليلي و أظهرت النتائج وجود مستوى مرتفع من الذكاء التنافسي في المؤسسة بمتوسطات حسابية مقبولة، كما كشفت النتائج عن وجود أثر ذو دلالة إحصائية عند مستوى معنوية (0.05) للذكاء التنافسي بأبعاده المختلفة على تحقيق القدرة التنافسية، مما يدل على أهمية توظيف الذكاء التنافسي كأداة استراتيجية لتعزيز أداء المؤسسة في بيئة تتسم بالمنافسة. "This study aims to identify the impact of competitive intelligence on achieving competitiveness in Algerian institutions. The focus was on the basic dimensions of competitive intelligence, namely: competitor and market intelligence, strategic intelligence, and technological intelligence, in addition to dimensions of competitiveness such as: outstanding efficiency, quality, flexibility, creativity, and innovation. Primary data were collected using a questionnaire specifically designed for the study, distributed to a sample of 35 employees at the Algerian Telecom Company in El Oued, representing different job levels. The data were analyzed using SPSS 28, where descriptive statistical methods were employed to measure the reality of competitive intelligence and competitiveness within the institution. Inferential statistical methods, such as simple linear regression analysis, were also used to test the study hypotheses. We also used the IMRAD model and the descriptive analytical approach. The results showed a high level of competitive intelligence in the institution, with acceptable arithmetic averages. The results also revealed a statistically significant effect at a significance level of (0.005) of competitive intelligence in its various dimensions on achieving competitiveness, indicating the importance of employing ,Competitive intelligence as a strategic tool to enhance organizational performance in a competitive environment.
ماستر علوم التسيير
Keywords: الذكاء التنافسي; القدرة التنافسية; الذكاء التكنولوجي; competitive intelligence; competitiveness; technological intelligence